2023
DOI: 10.1002/advs.202205445
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Deoptimization of Codons in SARS‐CoV‐2 and Related Implications for Vaccine Development

Abstract: The spread of coronavirus disease 2019 (COVID‐19), caused by severe respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has progressed into a global pandemic. To date, thousands of genetic variants have been identified among SARS‐CoV‐2 isolates collected from patients. Sequence analysis reveals that the codon adaptation index (CAI) values of viral sequences have decreased over time but with occasional fluctuations. Through evolution modeling, it is found that this phenomenon may result from the virus's mutation p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Although synonymous substitutions conventionally are thought to have no direct impact on protein structure or function, studies have demonstrated their role in changing virus fitness by altering the secondary structure of RNAs and modifying codon usage bias during replication [ 76 , 77 , 78 ]. These alterations may lead to a reduction in translation and replication efficiency, resulting in decreased infectivity during transmission and weakened protein expression during virus evolution [ 77 , 78 , 79 ]. The intricate interplay between synonymous and nonsynonymous mutations in the GVA population under natural selection pressure and their implications for pathogenicity and the evolution of GVA merits further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Although synonymous substitutions conventionally are thought to have no direct impact on protein structure or function, studies have demonstrated their role in changing virus fitness by altering the secondary structure of RNAs and modifying codon usage bias during replication [ 76 , 77 , 78 ]. These alterations may lead to a reduction in translation and replication efficiency, resulting in decreased infectivity during transmission and weakened protein expression during virus evolution [ 77 , 78 , 79 ]. The intricate interplay between synonymous and nonsynonymous mutations in the GVA population under natural selection pressure and their implications for pathogenicity and the evolution of GVA merits further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Codon optimization has played an important role in the development of RNA-based COVID-19 vaccines. Current research efforts are focused on further advancing the field of codon optimization for COVID-19 vaccines to address new strains of the coronavirus ( Wu et al, 2023 ). Unfortunately, it was not possible to provide here the specific metrics used for codon optimization in the above-mentioned studies for commercial product development.…”
Section: Future Directionsmentioning
confidence: 99%